A Day with No Words - Hammond, Tiffany; Cosgrove, Kate (New Egypt, NJ : Wheat Penny Press, 2023)
"A must-read that belongs in every home and classroom, A Day With No Words invites readers into the life of an Autism Family who communicates just as the child does, without spoken language."--.
New Kids Book Winter 2024.
Keywords: Families -- Juvenile fiction; Autistic people -- Juvenile fiction; Autistic children -- Juvenile fiction; Mothers of autistic children -- Juvenile fiction; Nonverbal communication -- Juvenile fiction; Neurodiversity -- Juvenile fiction; Mother and child -- Juvenile fiction; Picture books